The Evaluation of Puskesmas Information System (Simpus) Implementation of Puskesmas X in Kediri City - Reny Nugraheni; Katmini (International Journal of Seocology, 2020)
In accordance with the evaluation results of the Ministry of Health of the Republic of Indonesia in the Strategic Plan of the Ministry of the Republic of Indonesia in 2010-2014. The existence of data in the era of decentralization has become weak, the need for data and information for evidence planning is not available on time, even though the National Health Information System (Siknas) online has been integrated. Puskesmas is the spearhead of the National health data source. So it is important to evaluate the implementation of SIMPUS in the Puskesmas X Kediri City. Objective: To find out the Evaluation of the Implementation of Puskesmas Information System (Simpus) at Sukorame Puskesmas Kediri City in 2018. Method: The design of this research is quantitative descriptive. Data collection techniques were carried out by observation and interviews with the input variables, process, and output of the SIMPUS Puskesmas X Kediri City. Results: the study showed that the input aspects of SIMPUS were in accordance with the standards, namely there were HR data managers, namely the head of administrative staff, infrastructure facilities, namely computers and internet. For aspects of the Simpus process there is still incomplete patient data recording, and reporting online, week and month online is 80% late. For the aspect of Simpus output, which is that the accuracy of the data is still incomplete and the reporting time for incoming data at the Health Office for 1 year is 80% late. Conclusion: SIMPUS implementation in Puskesmas X Kediri City has not run optimally. Suggestion: The Health Office needs to create a simpler Simpus and each Puskesmas needs special experts for data managers.